PENGARUH KOMPENSASI DAN PROMOSI JABATAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. PERMATA JAGA KARYA, DENPASAR - Sapta Rini Widyawati; Prita Ayu Kusumawardhany (Forum Manajemen, 2020)
This study aims to determine the effect of compensation and job promotions on employee job satisfaction at PT. Permata Jaga Karya, Denpasar. The number of research samples were 84 employees. Determination of the sample using saturated or census means that all employees are respondents. The analytical tool used is multiple linear regression analysis with the help of SPSS version 23.0. The results of the analysis showed that compensation had a significant positive and significant effect on employee job satisfaction at PT. Permata Jaga Karya, Denpasar, this is evidenced by the value of the coefficient B for X1 is positive and the significant value of t (X1) <0.05. Similarly, promotion has a significant positive and significant effect on employee job satisfaction at PT. Permata Jaga Karya, Denpasar, this is evidenced by the value of the coefficient B X2 is positive and the significant value of t (X2) <0.05.